The Use of Ventilation Emissions Heat On The Basis Of Wasteheat Exchangers - Aleksandr Ya. Shelginsky, Margarita N. Stepanenko; Aleksandr Ya. Shelginsky, Margarita N. Stepanenko (International Journal of Advanced Science and Technology, 2020)
This research describes a result of the comparative analysis of the energy efficiency of the use of the ventilation emissions heat for heating the inlet air. The papers analysis is based on comparison of the once-through ventilation systems power inputs with a wasteheat exchanger and without it. The research was carried out with the use of fundamental laws of engineering thermodynamics, heat-mass exchange, hydraulics; mathematical apparatus of statistics; heuristic methods of synthesis of new structural and parametric solutions; methods of simulating the heat-mass-exchange processes; the obtained results agreement with the experimental data. The comparative analysis results are cited in the context of specific production premises. The power inputs comparison is represented on the thermal energy saving and the power use. The standard fuel consumption comparison is cited too. This research covers the results of prospects of the wasteheat exchangers application for the efficient use of the ventilation emissions heat. For the first time, the results of feasibility study of the various ventilation systems efficiency with account taken of the capital, operating costs and the regions’ climatic conditions were obtained.